Comparing Standing Heat and Estrotect Heat Detection Patches - S. K. Johnson; J. R. Jaeger (Kansas Agricultural Experiment Station Research Reports, 2016)
A recent survey showed that 66% of producers surveyed used some amount of heat detection in their artificial insemination program, and 74% of producers that used heat detection aids had tried Estrotect (Rockway, Inc.; Spring Valley, WS) heat detection patches. The peel-and-stick application made Estrotect more popular than types that required adhesive application. The patches are designed so that when the animal is mounted the top surface layer is removed, much like scratching a lottery ticket. After several mounts the entire layer is removed, leaving a bright-colored surface behind. A new type of patch, Standing Heat (Standing Heat, LLC; Dannebrog, NE), was recently released and has a surface layer designed to rub off with the goal of reducing false positive readings due to inadvertent scratches such as from branches or tail switching. The objective of the current study was to compare the efficacy of two different heat detection patches.
Keywords: Beef Cattle Research